معاني ألفاظ اليسر والعسر وما يشتق منهما في القرآن الكريم - Wahyudin, Dedih; Husna Hamzah, Tina Asmaul (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2020)
This study aims to determine the lexical meaning, contextual meaning, and educational implications of the words